Allocating Losses: Bail-ins, Bailouts and Bank Regulation - Todd Keister; Yuliyan Mitkov (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
We study the interaction between a government's bailout policy and banks' willingness to impose losses on (or in") their investors. The government has limited commitment and may choose to bail out banks facing large losses. The anticipation of this bailout undermines a bank's private incentive to impose a bail-in. In the resulting equilibrium, bail-ins are too small and bailouts are too large. Some banks may also face a run by informed investors, creating further distortions and leading to larger bailouts. We show how a regulator with limited information can raise welfare and improve financial stability by imposing a system-wide, mandatory bail-in at the onset of a crisis. In some situations, allowing banks to choose between meeting a minimum bail-in and opting out can raise welfare further.
Keywords: E61; G18; G28; 330; Bank bailouts; moral hazard; financial stability; banking regulation